Virtual Network Functions Deployment between Business Expectations and Technical Challenges: The T-NOVA Approach - Rebahi, Yacine; S. Ghamsi, Majid; Herbaut, Nicolas; Negru, Daniel; M. Comi, Paolo; S. Crosta, Paolo; Lorenz, Pascal; Pallis, Evangelos; Markakis, Evangelos (Recent Advances in Communications and Networking Technology, 2016)
Background: This paper belongs to the series of research documents describing the progress in the specification and development of the T-NOVA framework offering a marketplace for virtual network functions. T-NOVA is an international research project co-funded by the European Commission. Objective: Although, the idea of having a marketplace enabling buying, composing, and deploying “virtual” services on the fly is promising, its implementation or prototyping remains far from realization. This is mainly due to the limitations in the existing cloud computing platforms on top of which the services should be built. Method: In this paper, we discuss the T-NOVA approach and in particular some of the Virtual Network Functions (VNFs) that have been developed in this context. Special attention is paid to the design and specification of the VNFs as well as the related technical challenges that were faced when deployed within the marketplace. Results: Real-world considerations for handling VNF Lifecycles, Monitoring and Networking have also been discussed. We have highlighted two examples of Service Chaining where several VNFs are combined through the T-NOVA Marketplace to create added-value services. Some experiments and test results are also provided. Conclusion: In this paper, we have provided an overview on the T-NOVA Platform with a special focus on the deployment and performances of a wide variety of Virtual Network Functions implemented during the project. It is expected that the challenges and opportunities described in this paper will help foster innovation around NFV and will help pave the way for practitioners and researchers alike to further extend the use of Network Function virtualization in the future.
Keywords: marketplace